Acquisition of chromosome 1q duplication in parental and genome‐edited human‐induced pluripotent stem cell‐derived neural stem cells results in their higher proliferation rate in vitro and in vivo. (12th September 2020) - Mehrjardi, Narges Zare; Molcanyi, Marek; Hatay, Firuze Fulya; Timmer, Marco; Shahbazi, Ebrahim; Ackermann, Justus P.; Herms, Stefan; Heilmann‐Heimbach, Stefanie; Wunderlich, Thomas F.; Prochnow, Nora; Haghikia, Aiden; Lampert, Angelika; et al.
Abstract: Objectives: Genetic engineering of human‐induced pluripotent stem cell‐derived neural stem cells (hiPSC‐NSC) may increase the risk of genomic aberrations. Therefore, we asked whether genetic modification of hiPSC‐NSCs exacerbates chromosomal abnormalities that may occur during passaging and whether they may cause any functional perturbations in NSCs in vitro and in vivo. Materials and Methods: The transgenic cassette was inserted into the AAVS1 locus, and the genetic integrity of zinc‐finger nuclease (ZFN)‐modified hiPSC‐NSCs was assessed by the SNP‐based karyotyping. The hiPSC‐NSC proliferation was assessed in vitro by the EdU incorporation assay and in vivo by staining of brain slices with Ki‐67 antibody at 2 and 8 weeks after transplantation of ZFN‐NSCs with and without chromosomal aberration into the striatum of immunodeficient rats. Results: During early passages, no chromosomal abnormalities were detected in unmodified or ZFN‐modified hiPSC‐NSCs. However, at higher passages both cell populations acquired duplication of the entire long arm of chromosome 1, dup(1)q. ZNF‐NSCs carrying dup(1)q exhibited higher proliferation rate than karyotypically intact cells, which was partly mediated by increased expression of AKT3 located on Chr1q. Compared to karyotypically normal ZNF‐NSCs, cells with dup(1)q also exhibited increased proliferation in vivo 2 weeks, but not 2 months, after transplantation. Conclusions: These results demonstrate that, independently of ZFN‐editing, hiPSC‐NSCs have a propensity for acquiring dup(1)q and this aberration results in increased proliferation which might compromise downstream hiPSC‐NSC applications. Abstract : Neural stem cells (NSC) derived from human induced pluripotent stem cells (hiPSC) maintain genomic stability in vitro during early passages, irrespective of whether they were genetically engineered using zinc finger nucleases (ZFN) or not. However, prolonged passaging both of non‐modified or ZFN‐modified clonal NSC sublines leads to acquisition of duplication of the entire long arm of chromosome 1 [dup(1)q]. This aberration increases the proliferation of hiPSC‐NSC in vitro which is most likely mediated by upregulation of AKT3 located on the duplicated chromosome. Higher proliferation rate of hiPSC‐derived NSCs carrying dup(1)q is retained in vivo after two weeks of transplantation into the striatum of immunodeficient rats. Although monitoring of animals for two months did not reveal any tumor formation from transplanted NSCs in both experimental groups, the presence of dup(1)q may poses a tumorigenic risk at later time points and represent a significant obstacle to use of hiPSC‐NSC for research and therapy.